Influence of child's individual experience on motor activity skill development during the preschool period / Valentina V. Grebneva, Marina V. Sadovski and Alexey Yu. Kovtunenko - V. Grebneva, Valentina; V. Sadovski, Marina; Kovtunenko, Alexey Yu (Universiti Teknologi MARA, 2021)
The advent of technology has overshadowed children's leisure time and deprived them of the opportunity for physical activity. The main target of the current study is to discuss about the methodology of individualized diagnostics of motor activity peculiarities among children during the preschool period. The aspect of physical activity development is of federal importance. The research problem is presented as a search for pedagogical possibilities to optimize the motor activity of a growing person during preschool age. The characteristics of a child's motor activity and transformation factors are described when deviating from the age norm, both in the negative and in the positive direction. In the course of the study, the results were obtained that testify to the high efficiency of diagnostic techniques aimed at identifying the features of the motor activity of children in different types of preschool educational institutions. Distribution of the sample according to the behavioral characteristics of motor activity is possible; according to the profile of the main needs of the subjects and the emotional attitudes of preschoolers to different types of physical activity using color choices.